Aircrew training and assessment - O'Neil, Harold F.; Andrews, Dee H. (Human factors in transpartation, 2010)
Aircrew Training and Assessment is designed for professionals in the aviation psychology, human factors, assessment and evaluation, vocational, technical, educational psychology, and educational technology communities. It explores the state of the art in the training and assessment of aircrews and includes a review and description of the use of simulations in the area of aircrew training and assessment. An aircrew consists of one or more persons who are responsible for achieving a mission goal through use of an aircraft. Depending on one's point of view, an aircrew can be as small as one pilot flying a single-seat aircraft, or as large as a full crew operating an airliner. Despite advances in aircrew selection and human factors engineering techniques, the need for better aircrew training is still readily apparent. For example, in the military, the missions requiring aircrews keep getting more complex. Simulation is used extensively in both military and civilian training to deal with this complexity. The book is organized into two major sections: models and tools for training of aircrews and models and tools for assessment of aircrew training. Both military and civilian environments are covered, as well as individual and team training.